The Brain of Teleost Fish, a Source, and a Target of Sexual Steroids - Diotel, Nicolas; Do-Rego, Jean-Luc; Anglade, Isabelle; Vaillant, Colette; Pellegrini, Elisabeth; Vaudry, Hubert; Kah, Olivier (Frontiers in Neuroscience, 2011)
Neurosteroids are defined as steroids de novo synthesized in the central nervous system. While the production of neurosteroids is well documented in mammals or amphibians, there is little information in teleosts, the largest group of fish. Teleosts have long been known for their high brain aromatase and 5α-reductase activities, but recent data now document the capacity of the brain of fish to produce a large variety of sex steroids. This article aims at reviewing the available information regarding expression and/or activity of the main steroidogenic enzymes in the brain of fish. In addition, the distribution of estrogen, androgen and progesterone nuclear receptors is documented in relation with the potential sites of production of neurosteroids. Interestingly, radial glial cells acting as neuronal progenitors, appear to be a potential source of neurosteroids, but also a target for centrally and/or peripherally produced steroids.